Regulation of Na+ fluxes in plants - Maathuis, Frans J. M.; Ahmad, Izhar; Patishtan, Juan (Frontiers in Plant Science, 2014)
When exposed to salt, every plant takes up Na+ from the environment. Once in the symplast, Na+ is distributed within cells and between different tissues and organs. There it can help to lower the cellular water potential but also exert potentially toxic effects. Control of Na+ fluxes is therefore crucial and indeed, research shows that the divergence between salt tolerant and salt sensitive plants is not due to a variation in transporter types but rather originates in the control of uptake and internal Na+ fluxes. A number of regulatory mechanisms has been identified based on signalling of Ca2+, cyclic nucleotides, reactive oxygen species, hormones, or on transcriptional and post translational changes of gene and protein expression. This review will give an overview of intra- and intercellular movement of Na+ in plants and will summarise our current ideas of how these fluxes are controlled and regulated in the early stages of salt stress.